Strategi Manajemen ASN Melalui Program Diklat Studi Kasus di Setjen DPD RI - Yuliati, Angger Dwi (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: Education and training are fundamental pillars in civil servant (ASN) management to ensure professionalism in public services. As a support organization for the constitutional responsibilities of the Regional Representative Council of the Republic of Indonesia (DPD RI), the Secretariat General of the DPD RI needs highly skilled workers to effectively perform its legislative, oversight, and budgeting tasks. Methodology/approach: This study uses the 9-Box Model to map the potential and actual capabilities of ASN, complemented by explanatory-analytical qualitative methods to analyze the relationship between human resources competencies and organizational needs. Results/findings: The results of the study show that this approach is able to identify competency gaps and design needs-based training programs, enabling the design of targeted training programs and improving ASN management efficacy and ensuring that ASN management functions are implemented effectively. Conclusions: Through this description, investment in human capital not only strengthens internal capacity but also becomes a catalyst for improving the quality of accountable and responsive public services. Limitations: The limitation of this study is that the scope of this study is still too narrow, namely only focusing on ASN in the Secretariat General of the DPD RI, so that the results of this study cannot necessarily be generalized to other government agencies that have different characteristics. Contribution: The implication of this study is the importance of integration between education, training, and talent management in creating an adaptive, innovative, and sustainable workforce.